Composite Energy Storage System with Photovoltaic Power Generation and Uninterruptible Power Supply Function - Jung-Min Kwon (International Journal of Photoenergy)
A composite energy storage system (CESS) that includes a photovoltaic (PV) power generation and an uninterruptible power supply (UPS) function is proposed. This system has three operating modes, namely, a grid-connected inverter mode, a grid-connected rectifier mode, and an islanding mode. This system is composed of a boost converter, a three-phase inverter/rectifier, a bidirectional DC/DC converter, and thyristor switches. The boost converter extracts maximum power from the PV panels and sends it to the DC-link. The bidirectional DC/DC converter is connected between the battery and the DC-link, which leads to an optimized charging/discharging operation. The three-phase inverter/rectifier transmits the power to and from the grid. Also, it operates as a UPS in the islanding mode. The thyristor switches are used for connecting/disconnecting between the grid and the AC load. A 15 kW prototype is implemented to verify the performance of the proposed system.